Hanna M. Frąckowiak, Proceedings before the Regional Commission for Evaluation of Medical Events, series: Monografie Prawnicze, Wydawnictwo C.H. Beck, Warszawa 2016, ss. 460, ISBN 978-83-255-8375-0. (by Paulina Jankowska) - Jankowska, Paulina (Studia Prawa Publicznego, 2019)
Hanna M. Frąckowiak, Proceedings before the Regional Commission for Evaluation of Medical Events, series: Monografie Prawnicze, Wydawnictwo C.H. Beck, Warszawa 2016 ss. 460, ISBN 978-83-255-8375-0. (by Paulina Jankowska)